Frames and Consensus Formation in International Relations: The Case of Trafficking in Persons - Charnysh, Volha (2015)
This article examines the process of consensus formation by the international community regarding how to confront the problem of trafficking in persons. We analyze the corpus of United Nations General Assembly Third Committee resolutions to show that: (1) consensus around the issue of how to confront trafficking in persons has increased over time; and (2) the formation of this consensus depends upon how the issue is framed. We test our argument by examining the characteristics of resolutions’ sponsors and discursive framing concepts such as crime, human rights, and the strength of enforcement language. We conclude that the consensus-formation process in international relations is more aptly described as one of ‘accommodation’ through issue linkage than a process of persuasion